2018
DOI: 10.1016/j.scriptamat.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Bauschinger effect in gradient structured copper

Abstract: Bauschinger effect is a well-known phenomenon, in which the tensile stress is higher than the reverse compressive stress. Here we report that the gradient structured copper exhibits an extraordinarily large Bauschinger effect. We propose to use the reverse yield softening, Δσ b , as a quantitative parameter to represent the Bauschinger effect. Δσ b evolves in the same trend as the back stress with pre-strain, and can be used to evaluate the effectiveness of a heterostructure in producing back stress for superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In the following, we will present a brief history of the back stress concept, instead of a comprehensive review. Back stress is often related to the Bauschinger effect because they have the same physical origin [36][37][38][39]. In 1886 Bauschinger found that after an alloy was deformed plastically in tension, it exhibited a compressive yield strength lower than its tensile yield strength, and vice versa [40].…”
Section: Brief History Of Back Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…In the following, we will present a brief history of the back stress concept, instead of a comprehensive review. Back stress is often related to the Bauschinger effect because they have the same physical origin [36][37][38][39]. In 1886 Bauschinger found that after an alloy was deformed plastically in tension, it exhibited a compressive yield strength lower than its tensile yield strength, and vice versa [40].…”
Section: Brief History Of Back Stressmentioning
confidence: 99%
“…Back stress has been considered playing a critical role in the strengthening of metal matrix composites [44][45][46]. It is also often associated with Bauschinger effect [36,38,47,50]. However, neither back stress nor Bauschinger effect has been regarded as a major player in strengthening metallic materials by the general materials community.…”
Section: Back Stress and Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such actual experimental evidence is not available in the literature on HGSs, such as refs. 54 56 , where it was only argued that such behavior may be possible. More directly, we observe that the increase in internal back stresses (see SI Appendix , Fig.…”
mentioning
confidence: 99%
“…In other words, dislocations gliding in the adjacent plastically deforming layers may be blocked and pile-up near the two elastic-plastic interfaces. The pile-up of GNDs generates long-range back stress in the plastic layer [15,[23][24][25][26][27][28][29][30][31]. The back stress needs to be balanced at the interfaces by forward-stress in the elastic layer, which contributes to the formation of the observed hardening belly, as shown in Figure 2(b).…”
Section: Resultsmentioning
confidence: 99%